Effects of colonization of an endophytic fungus, Hendersonia toruloidea on thiamine biosynthesis in oil palm seedlings (Elaeis guineensis Jacq.) - Kamarudin, Amirah Nor (2017)
Thiamine, or vitamin B1 plays an indispensable role in many metabolic reactions. Besides that, thiamine is also associated with the induction of systemic acquired resistance (SAR) in plants and having a role in boosting plant’s immunity and defense system. In Malaysia, oil palm productivity is hampered by basal stem rot disease caused by a pathogenic fungus, Ganoderma boninense and proper disease management have yet to be discovered. Application of endophytes as biocontrol agent is a promising measure to prevent the disease. Hendersonia toruloidea is an endophytic fungus originally isolated from oil palm roots which have been shown to have excellent biocontrol activity in oil palm seedlings. Previous studies showed that this endophyte is able to suppress G. boninense infection in oil palm seedlings. This work aimed to investigate the responses in oil palm seedlings, specifically on the expressions of thiamine biosynthesis genes upon application of H. toruloidea. Seven months old oil palm seedlings were inoculated with H. toruloidea and microscopy analyses were carried out to visualize the colonization of the fungus. Total RNA was extracted from oil palm leaves at day 1, 7, 15 and 30 post inoculation. Quantitative real-time PCR (qPCR) was performed to measure the level of expression of four key thiamine biosynthesis genes, namely THI4, THIC, TH1 and TPK. The results showed of up to 12-fold of increase in the expression of all gene transcripts at day 1 post inoculation. At subsequent days of day 7, day 15 and 30 post inoculation, the relative expression of these genes were shown to be downregulated. Thiamine accumulation was observed via HPLC analysis at day 7 post inoculation and subsequently attenuated until day 30. This work provides first evidence of enhancement of thiamine biosynthesis by endophytic colonization in oil palm and suggesting the role of thiamine in stress protection in oil palm seedlings.